Turkish version of the motor function measure scale (MFM-32) for neuromuscular diseases: A cross-cultural adaptation, reliability, and validity study - İnal, Habibe Serap; Tarakçı, Ela; Tarakçı, Devrim; Aksoy, Gülcan; Mergen Kılıç, Sezan; Beşer, Hakan; Beşer, Çiğdem; Özdinçler, Arzu Razak; Durmuş Tekçe, Hacer; Parman, Fatma Yeşim; Deymeer, Feza; Oflazer, Zehra Piraye (TUBİTAK Scientific & Technical Research Council Turkey, 2017)
Background/aim: The Motor Function Measure (MFM-32) is a classification system for ambulant and nonambulant patients with neuromuscular diseases (NMDs). We aimed to translate it into Turkish, culturally adapt it, and test its reliability and validity for Turkish patients with NMDs. Materials and methods: The translation of the 32 items assessing three functional areas: standing position and transfers (D1: 13), axial/proximal (D2: 12), and distal (D3: 7) motor functions was performed according to the established guidelines for cross-cultural adaptation. Totally 51 patients (12.56 +/- 8.84 years; F/M 12/39) were tested. Vignos and Brooke scores for the lower and upper extremities, respectively, were used for the validity of the MFM-32-TR items, which were rated on a 4-point Likert scale. Results: The agreement coefficients for interrater reliability were excellent (0.72-0.93) for 10 items, good (0.58-0.77) for 16 items, and moderate (0.42-0.56) for 6 items of the MFM-32-TR. The intertester reliability varied from good to excellent and the intraclass correlation coefficient was 0.76-0.93. The MFM-32-TR positively correlated with Vignos and Brooke scores with coefficients 0.47 to 0.75, indicating concurrent validity. Conclusion: The MFM-32-TR is a reliable and valid outcome measure for the assessment of motor function of people with NMDs in our sociocultural context.
WOS: 000418884300024
PubMed ID: 29306245
Keywords: Neuromuscular Diseases; Motor Functions; Cultural Adaptation; Validity; Reliability